The Glycoprotein Ib-IX-V Complex in Platelet Adhesion and Signaling - Andrews, Robert K.; Shen, Yang; Gardiner, Elizabeth E.; Dong, Jing-fei; López, José A.; Berndt, Michael C. (Thrombosis and Haemostasis, 1999)
Thrombosis can result in unstable angina, acute myocardial infarction, or stroke, all major causes of death in the Western world. Circulating platelets become adherent and form an occlusive thrombus, either by exposure to sclerotic lesions following plaque rupture or in response to pathological shear stress in obstructed coronary arteries. This process parallels normal haemostasis, where platelets adhere to the subendothelium at sites of vascular injury, become activated, and recruit additional platelets to the developing thrombus. At high shear, thrombus formation is initiated by a specific platelet membrane adhesion receptor, the glycoprotein (GP) Ib-IX-V complex, which binds the adhesive glycoprotein, von Willebrand factor (vWF), in the vessel wall or plasma. Recent evidence also suggests that platelet adhesion to endothelial cells and leukocytes may be involved in atherogenesis, thrombosis, and inflammation. Preliminary findings indicate that GP Ib-IX-V specifically recognizes P-selectin, a member of the selectin superfamily, an interaction that may, at least partially, regulate platelet-endothelial cell adhesion. This review focuses on recent advances in understanding structure-activity relationships of GP Ib-IX-V.